Intimate Partner Violence and Femicide in Ecuador - Boira, Santiago; Tomas-Aragones, Lucia; Rivera, Nury (Qualitative Sociology Review, 2017)
This article analyzes intimate partner violence and femicide in Ecuador from an ecological perspective. The qualitative study, involving the participation of 61 individuals, took place in the province of Imbabura and was based on eight interviews with qualified experts and seven focus groups made up of professionals from the field of social and public services. The study comprises: a) the characterization of the dynamic of violence and risk of femicide; b) the analysis of the microsystem in relation to the family, neighbors, and professionals; c) an examination of the institutional response; and d) the assessment of the patriarchal culture, the role of the church, and indigenism. The results point to the permanence of a naturalized, chauvinistic culture, the lack of an effective network of resources to support victims, and a rigid administrative structure. As a consequence, victims have little confidence in public institutions, rates of reporting and prosecuting cases of violence are very low, and there is a perception that the aggressors are able to act with impunity, increasing the risk of severe violence and femicide.